Methodology for assessing risk in innovation investments - Belotti, Vitor Novelini; Santos, David Ferreira Lopes; Basso, Leonardo Fernando Cruz (Revista de Administração da UFSM, 2019)
The aim of this research is to analyze a theoretical method for measuring the business risk of investments in innovation proposed by Basso and Kimura (2010). The bases of the conceptual model relate the risk of investments in innovation at the firm level to the risk of the sector. In an analogous way, this study measures the sectorial risk of the different Brazilian industries with the added risk of investments in innovation, and then shows the risks of the companies listed on B3 (the São Paulo Stock Exchange) that exhibited all the necessary information for the model. This is an exploratory study with a quantitative approach, based on descriptive statistical methods and the proposed empirical model. The materials that support the research were taken from the five available editions of the Technological Innovation Survey – PINTEC (2000, 2003, 2005, 2008 and 2011) and from the standardized financial statements of the selected companies. The results of the research confirmed the possibility of using the proposed methodology, with the use of weighted factors that – in this study – were guided by the Brazil Innovation Index. Thus, it was possible to measure the level of risk of each sector of Brazilian industry and of 85 companies.